MENJADI GURU YANG TANGGUH DALAM PERSPEKTIF KRISTIANI: STUDI HUMANISASI PERAN PENDIDIK DALAM KONTEKS PENDIDIKAN AGAMA KRISTEN MASA KINI - suhendra, Suhendra; Adriaansz, Rinetje; Siauta, Shirley; lase, Ideniar lase (UPPM Sekolah Tinggi Teologi Tabgha Batam, 2025)
The role of teachers in education is not limited to the delivery of material and theory but also involves shaping the character and faith of students, particularly in the context of Christian Religious Education (CRE). In an era of rapid development, teachers face numerous challenges such as professional pressure, technological advancement, and a crisis of humanity in educational relationships. Therefore, there is a need for resilient teachers—both in terms of faith and character. This study aims to examine teacher resilience from a Christian perspective using a humanization approach to education. The formal object of this study is Christian Religious Education, while the material object is teacher resilience, understood as a manifestation of perseverance, faithfulness, and divine calling. The research method employed is qualitative, utilizing literature reviews from theological and pedagogical sources. The findings indicate that teacher resilience in the Christian faith is rooted in a deep relationship with Christ, a spirituality of service, and an understanding of one’s vocation as an educator. This study emphasizes that faith formation and character development are essential aspects in addressing the humanitarian crisis in today’s educational landscape. The research contributes to the development of a CRE curriculum that focuses on the holistic human needs of both teachers and students.